Olga Beloborodova, editor. The Making of Samuel Beckett’s Play/Comédie and Film. Bloomsbury, 2019. - S. E. Gontarski (Studies in 20th & 21st Century Literature, 2021)
Review of Olga Beloborodova, editor. The Making of Samuel Beckett’s Play/Comédie and Film. Bloomsbury, 2019. 352 pp.
Keywords: Beckett; digital humanities; textual studies; film; theater